{Practice changes in childhood surgery for ambiguous genitalia?} - Michala, L.; Liao, L.-M.; Wood, D; Conway, G.S.; Creighton, S.M. (Journal of Pediatric Urology, 2014)
© 2014 Journal of Pediatric Urology Company. Published by Elsevier Ltd. All rights reserved. (S.M. Creighton). Objective: In 2001, this team published an observational study of the clinical outcomes of a cohort of adolescent girls born with ambiguous genitalia. The poor outcomes observed represented a major scientific challenge to the standard practice of childhood feminising genital surgery. That publication was one of several contributing to a call for change in surgical practice, which culminated in the publication of the Chicago Consensus Document in 2006. The aim of this current study was to repeat the same evaluation of clinical outcomes on a recent cohort of adolescent girls and compare the two cohorts to identify differences in adolescent outcomes which may indicate a change in paediatric surgical practice. Methods: This was an observational study of a current cohort of adolescent girls treated in childhood for ambiguous genitalia and referred to a specialist adolescent disorders of sex development (DSD) service for assessment. Data were collected on surgical history, genital examination findings and treatment recommendations for 30 consecutive adolescents over a 5-year period. Findings were compared with those of a similar cohort of adolescent girls published over a decade previously. Results: Clitoral surgery remained common (93{%} vs 100{%}, current cohort vs historical cohort). However, concomitant vaginoplasty was performed less frequently (80 vs 100{%} current vs historical). Vaginoplasty revision surgery was also less commonly required (65 vs 81{%}), although 24{%} of the recent cohort still required major revision surgery prior to intercourse. There was some improvement to the cosmetic outcomes as deemed by the surgical team using the same criteria as the previous report. Conclusions: This study provides someslight evidence of recent practice change.Therewas asmall reduction in the number of vaginoplasties performed in childhood and an improvement in vaginoplasty outcomes and cosmesis.However, therewas no identifiable change inmanagement of clitoromegaly and the numbers of clitoral reduction operations remained high. This is surprising given the clear evidence of a detrimental impact of surgery on clitoral sensation and sexual function.
Keywords: Ambiguous genitalia; CAH; Childhood feminising genital surgery; Clitoroplasty; Disorders of Sex Development; Vaginoplasty